Praktik Politik Uang Pada Pemilihan Presiden (PILPRES) Tahun 2024 di Desa Widodaren Kecamatan Petarukan Kabupaten Pemalang - Palupi, Ivodia -; -, fitriyah -; Sardini, nur hidayat - (Journal of Politic and Government Studies, 2025)
Money politics is a phenomenon that often occurs in the context of general elections, including in the 2024 Presidential Election (Pilpres). In this research, the author examines the practice of money politics carried out by the presidential candidate success team in Widodaren Village, Petarukan District, Pemalang Regency. This research aims to understand how these practices influence people's choices and local political dynamics. The practice of money politics is carried out with various strategies aimed at: attract attention and support from voters. Successful teams seek to influence voter decisions through various means, including giving money, goods, or attractive promises. This research also highlights the factors that influence the occurrence of money politics, as well as the actors involved in this practice.Through a qualitative approach, the author collects data from various sources, including interviews with voters, direct observation, and document analysis. The data obtained was then analyzed to provide a comprehensive picture of the practice of money politics in the region. It is hoped that this research can contribute to understanding the impact of money politics in general elections. The research results show that money politics has a significant influence on people's choices in Widodaren Village. People tend to vote for candidates who provide rewards, even though they realize that this practice is unethical. These findings emphasize the need for efforts to increase public awareness about the negative impact of money politics and the importance of integrity in the general election process